Soil morphological and chemical characteristics in the habitats of the rare, endemic plant Spiraeanthus schrenkianus in Karatau Mountains, Kazakhstan - A. Muratbayeva; А. Nurmahanova; K. Kulymbet; A. Myltykbayeva; A. Akhmetova; B. Abdullayeva; S. Atabayeva; G. Baitasheva; E. Kyrbassova; Z. Omarova (Brazilian Journal of Biology)
Abstract The article presents the results of the study of ecological characteristics of soils of three populations on the territory of Karatau. The populations were located in different geographical points with differences in soil types, depth of horizons and content of chemical elements. The study evaluated the main soil parameters including humus content, pH, CO2, macro- and microelements, and salinity level. It was found that population-1 (mountain gray-brown soils) was characterized by the highest content of humus and mobile nitrogen, indicating better availability of nutrients to plants. population-2 (mountain southern serozems) has higher potassium content, which is favourable for plant growth. population-3 (mountain gray-brown soils) showed the lowest content of mobile phosphorus and copper compared to other populations. Analysis of heavy metal concentrations showed that zinc exceeded the maximum permissible concentration only in population-2. At the same time, soil salinization at all three sites remains at a low level and does not pose a threat to the ecosystem. These findings are ecologically significant as they reveal the critical role of soil fertility and contamination in supporting the distribution and survival of the rare endemic species Spiraeanthus schrenkianus. These results provide new information for assessing the fertility and sustainability of land resources.